Managing visitors' dining and retail experiences in South African national parks - M. Kruger; M. Saayman; E. Slabbert (South African Journal of Business Management, 2015)
In the light of the Issue of declining government funding of South African National Parks (SANParks), as well as the negative influence of the poor service levels in shops, restaurants and eating facilities in these parks on visitor spending, SANParks needs to improve the retail and dining experiences at these facilities. This research attempts to provide guidelines for SANParks management in addressing these Issues, by determining visitors' retail and dining preferences and the relationship between these constructs. Quantitative research was conducted in 2011 using a web-based survey on the SANParks' official website for two months (1st October – 30th November). This method resulted in obtaining 5 464 usable responses for the study. Factor analyses identified three relevant dining experience factors: Quality, Variety and value and Nature ambience and four retail experience factors: Goods and services, Pricing (consisting of two separate constructs: Expensive shops and Pay more inside Park) and Quality. To the best of the authors' knowledge, this was the first time that research was conducted with regard to addressing visitors' retail and dining preferences at any South African national park, thereby contributing significantly to literature regarding visitor experiences in a nature-based context.
Keywords: 650